Oncological Outcomes Following Surgical Management Of Localised Renal Cancer: A Comprehensive Systematic Review - Ridwan; Dhiba, Alsa Fara (The International Journal of Medical Science and Health Research, 2024)
Background: This study aims to serve a comprehensive systematic review on the oncological outcomes following surgical management of localised renal cancer in literatures of the last 5 years. Methods: The systematic review followed PRISMA 2020 standards and examined full-text English literature published between 2019 and 2024. This review excluded editorials, review papers from the same journal, and submissions without a DOI. Literature was sourced from online platforms such as PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  8,824 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: The evolving management of renal cancer emphasizes balancing oncologic effectiveness with preserving renal function. With PN's acceptance and minimally invasive options, tailored treatments improve outcomes. However, personalized decisions based on tumor and patient factors remain crucial for optimal results.